2010
DOI: 10.1016/j.bbadis.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid fibrillation and cytotoxicity of insulin are inhibited by the amphiphilic surfactants

Abstract: Amyloid fibrils have been associated with at least 25 different degenerative diseases. The 51-residue polypeptide hormone insulin, which is associated with type II diabetes, has been shown to self-assemble to form amyloid fibrils in vitro. With bovine insulin as a model, the research presented here explores the effects of two amphiphilic surfactants (1,2-dihexanoyl-sn-glycero-3-phosphocholine (di-C7-PC) and 1,2-diheptanoyl-sn-glycero-3-phosphocholine (di-C7-PC)) on the in vitro fibrillation process of bovine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 109 publications
0
48
1
Order By: Relevance
“…77 In addition, it was found that submicellar DHPC concentrations (below 8 mM) decelerate insulin aggregation, while at the same concentrations, no conformational transitions of the protein solution structure could be detected by CD. 78 Our current textbook view on lipids in living organisms is dominated by the concept of intact lipid bilayers, which enclose the cells as plasma membranes or define certain intracellular compartments, such as Golgi apparatus, endoplasmic reticulum and a plethora of different vesicular structures. However, it is important to note that lipids may naturally occur also outside these well-defined lipid compartments, although there is little information about the extent to which this happens.…”
Section: Discussionmentioning
confidence: 99%
“…77 In addition, it was found that submicellar DHPC concentrations (below 8 mM) decelerate insulin aggregation, while at the same concentrations, no conformational transitions of the protein solution structure could be detected by CD. 78 Our current textbook view on lipids in living organisms is dominated by the concept of intact lipid bilayers, which enclose the cells as plasma membranes or define certain intracellular compartments, such as Golgi apparatus, endoplasmic reticulum and a plethora of different vesicular structures. However, it is important to note that lipids may naturally occur also outside these well-defined lipid compartments, although there is little information about the extent to which this happens.…”
Section: Discussionmentioning
confidence: 99%
“…19 At present, no medication is available for AD, but there are evidences suggesting that reduction of amyloid assemblies can be favorable for animals and cells models of amyloidosis. 15,[20][21][22] Morgan et al have shown that laminin-1 can cause complete disassembly of fibrils into protofilaments and amorphous aggregates. 23 Fibril disaggregation induced by laminin-1 also contributed to the prevention of amyloid toxicity on hippocampal neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of insulin inhibition induced by (−)-epigallocatechin-3-gallate (EGCG) were selected from Wang et al [31], methylglyoxal effects were collected from Oliveira et al [32] and those produced by 1,2-diheptanoyl-sn-glycero-3-phosphocholine (di-C7-PC) were described in Wang et al [33]. Two conditions of EGCG affecting to fibrillation kinetics were used: EGCG_1 (case 1) studied at pH = 2.0/T = 60°C and EGCG_2 (case 2) at pH = 7.4/T = 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The meanings of other symbolic notations as well as the corresponding units are summarized in Table 1. In the experimental data chosen, the dependent variable of response or time-dependent signals ( X ) to detect amyloid protein aggregation were absorbance at 600 nm (data obtained from Wang et al [31]), relative ThT fluorescence intensity (%) (data from Wang et al [33]) and ThT fluorescence intensity at 482 nm or 490 nm (data obtained from Thapa et al [16]; Kanapathipillaia et al [15]; Oliveira et al [32] and Vilasi et al [34]).…”
Section: Methodsmentioning
confidence: 99%